Integrated thinking and reporting process: Sensemaking of internal actors in the case of Itaú Unibanco - Kelli Juliane Favato; Marguit Neumann; Simone Leticia Raimundini Sanches; Manuel Castelo Branco; Daniel Ramos Nogueira (Journal of Risk and Financial Management, 2021)
This study aims to understand the meaning created by Itaú Unibanco's internal actors in the Integrated Reporting (IR) processes. An interpretative approach based on Karl Weick's sensemaking perspective is adopted. A case study methodology was adopted for undertaking the empirical work. The results show that IR identity in the institution is related to three issues: synergy processes between sectors; integration for the production of other reports; and development of an integrated thinking chain for the entire business. We present perceptions on benefits and difficulties in the process of preparing the integrated report. Although the practices and processes established did not change the characteristics of the bank, the perspective of the social actors seems to have changed from a sectoral view to a multidimensional view. In addition, the conclusions suggest that it is not difficult to understand that separating 'thinking' from 'doing', attributing to the individual the role of mere operationalization is tantamount to ignore the meaning attributed to the organization's journey towards the creation of a process, namely the IR one. The study's contribution lies in pointing out that the IR process is directly related to the integrated thinking process. This could be the most significant differential of IR as a form of corporate communication as it amounts to a new reporting framework that proposes integrating social, environmental, and governance disclosures (non-financial information) with financial disclosures in a single report.
Keywords: 330; ESG reporting; integrated reporting; integrated thinking; sensemaking